(untitled) (Al-Qantara, 2024)
This study investigates the social connotations and symbolic meanings associated with colloquial terms related to women in spoken language. Focusing on how language both reflects and reinforces social attitudes, this research examines commonly used colloquial words and phrases, analyzing their underlying implications and the cultural values they convey. Through a combination of linguistic analysis and interviews, this study highlights the ways in which informal language can perpetuate stereotypes or reflect shifts in societal perspectives on gender. Findings reveal that certain colloquial terms carry significant symbolic weight, influencing perceptions of women in both subtle and explicit ways. This research provides insights into the intersection of language, gender, and social attitudes, offering a deeper understanding of how colloquial language both mirrors and shapes societal views of women. The results contribute to discussions on gender, language, and social change, providing a foundation for more inclusive language use.